Making sense of God incarnate: a neglected biblical resource - Philps, Mark (Theology, 2024)
The doctrine of the Incarnation raises important questions about the person of Christ and the nature of God. The John 5 discourse where Jesus speaks about what it means to be ‘the Son’ is a neglected source of insight into these questions. The article presents a case for reading this discourse as a statement about the eternal dependence of the Son. This interpretation is backed up by reference to the Synoptic Gospels, the writings of Paul and the work of Augustine. The article does not advocate an Arian ontological subordinationism but a proposal concerning the personhood of the Son. The conclusion sets out some of the gains of this approach.